3D Printing in Makerspaces: Health and Safety Concerns. - Neelam Bharti (Issues in Science and Technology Librarianship, 2017)
3D (three-dimensional) printing is included in makerspaces around the world and has become increasingly affordable and useful. Most makerspaces use Fused Deposition Modeling (FDM)-based 3D printers, using polylactic acid (PLA) and acrylonitrile butadiene styrene (ABS) as printing materials. However, heating PLA and ABS to high temperatures emits ultrafine particles and volatile organic compounds, which are potentially harmful and raise health and safety concerns. This paper discusses the health and safety hazards posed by 3D printing and presents recommendations to minimize the effects of these hazards. [ABSTRACT FROM AUTHOR]